Production technology and quality of corn silage for feeding dairy cattle in Southern Brazil - Mábio Silvan José da Silva; Clóves Cabreira Jobim; Edson Carlos Poppi; Tamara Tais Tres; Milene Puntel Osmari (Revista Brasileira de Zootecnia, 2015)
ABSTRACTThe objective of this study was to evaluate the production practices and use of corn silage in dairy farms in Southern Brazil, and to evaluate their impact on the nutritional quality and occurrence of mycotoxins. The data were collected by application of questionnaires among the producers, and by analysis of silage samples. The variables were subjected to factorial analysis of data reduction through the principal components method, thus obtaining 84.12% of the variance associated with the location, corn hybrid, crop production management, and inoculant used, characterizing the farms into four distinct groups. In farms from Paraná, the silage production technologies were more associated with implantation and crop management processes, and investment in equipment related to ensilage/silo feed-out was less frequent. Farms of Rio Grande do Sul showed high adoption of outsourced services, self-propelled machines, bunker silos, double-sided plastic film, and inoculant to control aerobic deterioration, and the silages showed higher levels of propionic acid (7.95 g/kg DM), and lower concentrations of aflatoxins (7.7 ppb) and total mycotoxins (26.58 ppb). The farms evaluated in Southern Brazil have good production efficiency and corn silages with excellent quality, regardless of their production characteristics.